Evaluation of Catchment area delineation Methods: Comparison of TOPAZ on WMS with HEC-HMS 4.12 - Setiyowati, Yunita Ayu (Geosfera Indonesia, 2025)
This research evaluates the results of the Jatigede Dam Catchment area delineation using two different methods, HEC-HMS 4.12 and WMS TOPAZ, by utilizing three Digital Elevation Model (DEM) resolutions: DEMNAS 8.29 m, ASTER 30m, and SRTM 90 m. The analysis results show that the higher the DEM resolution used, the greater the resulting area similarity between the two methods. At an SRTM resolution of 90 m, the resulting Catchment area is 1474.41 km² (WMS) and 1468.03 km² (HEC-HMS ). At 30 m ASTER resolution, the resulting Catchment area is 1467.88 km² (WMS) and 1465.03 km² (HEC-HMS ). Meanwhile, the DEMNAS resolution of 8.29 m shows a Catchment area of 1462.64 km² (WMS) and 1462.91 km² (HEC-HMS ). Significant differences in results are seen at lower DEM resolution, especially in the aspect of main river length and basin length, which is caused by limitations in topographic representation. At an SRTM resolution of 90 m, the resulting length of the main river is 44368.54 m (WMS) and 34960.17 m (HEC-HMS ), while at a DEMNAS resolution of 8.29 m the length of the main river reaches 58195.707 m (WMS) and 42537.38 m (HEC-HMS ). These findings emphasize the importance of choosing the right DEM resolution to achieve accurate and consistent delineation results, especially in hydrological applications.